Genetic Diversity and Phylogeography of Thottapalayam thottimvirus (Hantaviridae) in Asian House Shrew (Suncus murinus) in Eurasia - Kikuchi, Fuka; Aoki, Keita; Ohdachi, Satoshi D.; Tsuchiya, Kimiyuki; Motokawa, Masaharu; Jogahara, Takamichi; Sơn, Nguyễn Trường; Bawm, Saw; Lin, Kyaw San; Thwe, Thida Lay; Gamage, Chandika D.; Ranorosoa, Marie Claudine; et al. (Frontiers in Cellular and Infection Microbiology, 2020)
Rodents were formerly believed to be the only reservoir hosts of hantaviruses. However, the recent discovery of genetically distinct hantaviruses in shrews, moles and bats of multiple species suggests that the virus-host relationships are far more complex than previously recognized. The purpose of this study was to compare the genetic diversity and geographic distribution of Thottapalayam thottimvirus (TPMV) in Asian house shrews (Suncus murinus) from Asia, Africa and the Middle East. Comparison of TPMV genomic sequences from two Asian house shrews captured in Myanmar and Pakistan with TPMV strains in GenBank revealed that the Myanmar TPMV strain (H2763) was closely related to the prototype TPMV strain (VRC66412) from India. In the L-segment tree, on the other hand, the Pakistan TPMV strain (PK3629) appeared to be the most divergent, followed by TPMV strains from Nepal, then the Indian-Myanmar strains, and finally TPMV strains from China. The Myanmar strain of TPMV showed sequence similarity of 79.3–96.1 % at the nucleotide level, but the amino acid sequences of the encoded proteins were highly conserved with 94.1–99.2% similarity between TPMV strains from Nepal, India, Pakistan and China. Cophylogenetic analysis of host cytochrome b and TPMV strains suggested that the Pakistan TPMV strain was mismatched. Phylogenetic trees, based on host cytochrome b and cytochrome c oxidase subunit I genes of mitochondrial DNA, and on host recombination activating gene 1 of nuclear DNA, suggested that the Asian house shrew and Asian highland shrew (Suncus montanus) comprised a species complex. Overall, the geographic-specific clustering of TPMV strains in Asian countries suggested local host-specific adaptation. Additional in-depth studies are warranted to ascertain if TPMV originated in Asian house shrews on the Indian subcontinent.